2016
DOI: 10.1021/acsami.6b01655
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Transport at the LaAlO3/SrTiO3 Interface Explained by Microscopic Imaging of Channel-Flow over SrTiO3 Domains

Abstract: Oxide interfaces, including the LaAlO3/SrTiO3 interface, have been a subject of intense interest for over a decade due to their rich physics and potential as low-dimensional nanoelectronic systems. The field has reached the stage where efforts are invested in developing devices. It is critical now to understand the functionalities and limitations of such devices. Recent scanning probe measurements of the LaAlO3/SrTiO3 interface have revealed locally enhanced current flow and accumulation of charge along channe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 42 publications
8
47
1
Order By: Relevance
“…S3); (c) we compare V map with maps of the current flow obtained by scanning superconducting quantum interference device (SQUID). The configuration of the modulated current streaks over STO domains 20,25,26 is similar to the V map recorded simultaneously (Supplementary Information Fig. S4).…”
Section: (D) Illustration Top View Of [001] Twin Boundary Between Dosupporting
confidence: 64%
See 1 more Smart Citation
“…S3); (c) we compare V map with maps of the current flow obtained by scanning superconducting quantum interference device (SQUID). The configuration of the modulated current streaks over STO domains 20,25,26 is similar to the V map recorded simultaneously (Supplementary Information Fig. S4).…”
Section: (D) Illustration Top View Of [001] Twin Boundary Between Dosupporting
confidence: 64%
“…The domain wall polarization is highly anisotropic and Fig. 1c shows that below 40 K the ratio between two perpendicular measuring directions decays to values below unity 20,26 .…”
Section: (D) Illustration Top View Of [001] Twin Boundary Between Domentioning
confidence: 98%
“…[4,5] The most obvious manifestation of tetragonality is the anisotropy of the dielectric constant [6,7], which is responsible for the observed birefringence [8]. Recently, ferroelastic domain formation was shown [9][10][11] to strongly influence other electronic phenomena in SrTiO 3 , e.g., superconductivity [12] or two-dimensional electron gases [13][14][15]. The ability of controlling the electronic degrees of freedom by altering the ferroelastic domain structure provides, in principle, a tantalizing opportunity for new device concepts.…”
Section: Low-temperature Dielectric Anisotropy Driven By An Antiferromentioning
confidence: 99%
“…The difference was largest at low temperatures, but still appreciable at room temperature. Frenkel et al observed a weak anisotropy 35 associated with the channeling of currents along microstructural channels that changed on warming above the cubic to orthorhombic transition that occurs in STO at ∼ 105 K. Gopinadhan et al observed a weak anisotropy in the mobility of (110) samples at low temperatures 9 . In contrast to these previous observations, the anisotropy in the electrical characteristics of our (111) samples does not exist at room temperature or liquid nitrogen temperatures, and is reproducible even after repeated warming to room temperature.…”
Section: Sample Fabrication and Measurementmentioning
confidence: 99%